High sensitivity two photon absorption microcavity autocorrelator - Donegan, John; Bradley, Louise (My University, 2004)
A GaAs?AlAs microcavity device has been used as a photodetector in an autocorrelator for measuring the temporal pulsewidth of 1.5- m optical pulses. Enhancement of the two-photon absorption photocurrent due to the microcavity structure results in an autocorrelation (average power times peak power) sensitivity of 9 3 10 4 (mW)2, which represents two orders of magnitude improvement when compared with conventional autocorrelators
PUBLISHED
Keywords: nonlinear detection; photodetectors